2017
DOI: 10.1016/j.jns.2016.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Revised diagnostic criteria for neurocysticercosis

Abstract: This revised set of diagnostic criteria provides simpler definitions and may facilitate its more uniform and widespread applicability in different scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
230
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(244 citation statements)
references
References 67 publications
3
230
1
10
Order By: Relevance
“…The cysticerca can be found in the brain parenchyma, subarachnoidally, intraventricularly or in the spinal cord, as well as in the skeletal and cardiac muscles and other tissues [25,26].…”
Section: Cysticercosismentioning
confidence: 99%
“…The cysticerca can be found in the brain parenchyma, subarachnoidally, intraventricularly or in the spinal cord, as well as in the skeletal and cardiac muscles and other tissues [25,26].…”
Section: Cysticercosismentioning
confidence: 99%
“…Demonstration of cysticercus by histology or subretinal parasite by funduscopy form absolute criteria for diagnosis of cysticercosis 1. Chavala et al reported a 25-year-old pork handler with intraretinal cysticercosis associated with vision loss, and ocular ultrasound revealing retinal detachment with hypoechoic focus, which responded to antihelmintic therapy 2.…”
Section: Descriptionmentioning
confidence: 99%
“…Calcificação intracraniana é a apresentação mais comumente encontrada em NCC, cerca de 70% dos indivíduos acometidos, e representa a forma evolutiva final da doença [10][11][12][13][14][15][16][17] . Calcificações intracranianas podem ser encontradas em até 10% a 20% da população geral em regiões endêmicas [10][11][12][13][14][15][16] .…”
Section: Lista De Tabelasunclassified
“…Calcificações intracranianas podem ser encontradas em até 10% a 20% da população geral em regiões endêmicas [10][11][12][13][14][15][16] .…”
Section: Lista De Tabelasunclassified
See 1 more Smart Citation